The Effect of Organizational Culture, Motivation, and Self-Leadership on Student Performance In Start-Ups - Amalia Putri Ghassani; Wirawan ED Radianto; Stanislaus Mastan (School of Business, IPB University (SB-IPB), 2020)
The development of entrepreneurial education designed currently is developing rapidly. One of the goals of this education is to produce new start-ups. Therefore, factors that impact the performance of start-ups by university students are important to be studied further. This study aimed to determine the impact of organizational culture, motivation, and self-leadership on the performance of students of the Accountancy Study Program in a private university in Surabaya, which has entrepreneurship as part of their curriculum. This private university is a university with the vision of creating entrepreneurs. Therefore, the learning method provided is project-based learning. All students have to undergo entrepreneurship learning, and thus, they are required to create start-ups according to their field of study and according to their respective study program. The success of the students' start-ups will undoubtedly require excellent performance in achieving the set target. This study was conducted using a quantitative method and analyzed using multiple regression analysis. The result of this study suggested that organizational culture and self-leadership had an impact on students' performance in start-ups. However, motivation had no impact on students' performance in start-ups. Keywords: entrepreneurial education, organizational culture, performance, motivation, self-leadership